PERILAKU NELAYAN DALAM PENGELOLAAN WISATA BAHARI DI KAWASAN PANTAI LOVINA, BULELENG, BALI - Siti Amanah; Hamidah Nayati Utami (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2006)
Fishermen living around the Lovina Beach Tourism Area had other productive activities besides catching fishes. The fishermen living in coastal villages of Lovina offered services such as guides for tourists who were interested in diving, snorkeling, and watching dolphin’s attraction in their habitat. The objectives of this research were to portray the fishermen’s behavior in managing the tourism services and to determine the variables correlated to the fishermen behavior and the tourist satisfaction. The research showed that the fishermen’s competencies in managing the tourism related activities need improvement, especially in the management of coastal resources and services. Furthermore, all of the fishermen’ variables, whether internal or external, were positively and significantly correlated with their coastal tourism management behavior and the tourists satisfaction. It was recommended that along with the purposes of promoting tourism and the fishermen quality of life, learning programs that were developed based upon the fishermen’s problems and needs were required. The programs could include hospitality training, eco-tourism, and tourism management. Additionally, coordination amongst the fishermen groups, local government, non government organization, and private sector involved in these activities was needed to improve the performance of the tourism service.